Las dimensiones bioéticas en la jurisprudencia de la corte interamericana de derechos humanos. - Chacón Mata, Alfonso (2019)
This article deals with the analysis and characterization of those judgments issued by the Inter-American Court that have a direct relationship with “bioethical dimensions”. Bioethics is a relatively recent discipline, but its factual framework covers aspects of diverse nature, protecting the human being from abuses of scientific research, adequate information and access to medical treatments, the enjoyment of an adequate level of health without no discrimination whatsoever, and the validity of the right to life. The article includes at least three possible dimensions that have been developed in the jurisprudence of the Inter-American Court: human dignity, right to health and adequate medical practices, and clinical bioethics and the right to life.